Gender and age differences in anxiety sensitivity, anxiety and depression among school children in Croatia - Jokić-Begić, Nataša; Lauri Korajlija, Anita; Jurin, Tanja (2007)
OBJECTIVES: Symptoms of anxiety, anxiety sensitivity (the fear of anxiety sensations), and depression are very frequent in childhood. In most cases, they are a normal part of child development and disappear as the child grows up. In some children, however, these symptoms are pathological. AIM: To determine gender differences and differences in the intensity of anxiety sensitivity, anxiety and depression symptoms as a function of age in a non-clinical sample of children. METHOD: The study included 463 school children (47.1% boys) aged 11-14 years from two elementary schools. The children were tested with Childrenâ€ ™ s Anxiety Scale (SKAN), Childrenâ€ ™ s Depression Inventory (CDI), and Childhood Anxiety Sensitivity Index (CASI). RESULTS: Girls had higher anxiety sensitivity and trait anxiety index than boys, but there was no significant difference in the depression intensity scores. The intensity of anxiety and depressive symptoms increased with child age. Older children scored higher than younger ones on the anxiety and depression scales. There was a difference in the trend of anxiety sensitivity between girls and boys. Anxiety sensitivity in girls peaked at age 12 (6th grade) and then started showing a downward trend. In boys, the level of anxiety sensitivity remained unchanged until age 14 (8th grade), when it started decreasing dramatically. CONCLUSION: The intensity of anxiety and depression symptoms increased with child age. Anxiety intensity was higher among girls than among boys. More than anxiety and depression symptoms, anxiety sensitivity changed with age, peaking at age 12 among girls and age 14 among boys.
Projekt MZOS
ENG